Contribution of HLA‐B*51:01 and ‐A*26:01 to Behçet's disease and their clinical association in Thai patients. (15th January 2020) - Louthrenoo, Worawit; Kasitanon, Nuntana; Pathanapitoon, Kessara; Wangkaew, Suparaporn; Kuwata, Shoji; Nishi, Ai; Kaburaki, Toshikatsu; Tanaka, Rie; Takeuchi, Fujio
Abstract: Aims: To investigate susceptible human leukocyte antigen (HLA) alleles and their associations with clinical features in Thai patients with Behçet's disease (BD). Method: Eighteen HLA‐A and 36 HLA‐B alleles were determined in 42 Thai BD patients and 99 healthy controls (HCs) by reverse line blot assay, and reconfirmed by MICRO SSP assay. Results: The BD patients had significantly higher allele frequency (AF) of HLA‐B*51 than the HCs (13.10% vs 5.05%, P  = .025). The AF of HLA‐A*26, ‐A*26:01 and ‐B*51:01 also was higher and almost reached statistical significance (5.59% vs 1.52%, P  = .054, 5.95% vs 1.52%, P  = .054 and 10.71% vs 4.04%, P  = .051, respectively). However, the BD patients had significantly higher AF of either HLA‐A*26:01 or ‐B*51:01 (16.67% vs 5.56%, P  = .005), or ‐A*26:01 or ‐B*51X (19.05% vs 6.56%, P  = .003). The AF of HLA‐B*51:01 and ‐B*51X increased significantly in ‐A*26:01 non‐carrier BD patients (12.16% vs 4.17%, P  = .024 and 14.86% vs 5.21%, P  = .019, respectively); and that of HLA‐A*26:01 was significantly higher in ‐B*51X non‐carrier BD patients (7.58% vs 1.67%, P  = .034). HLA‐B*51:01 associated significantly with the presence of posterior uveitis and visual impairment (18.18% vs 2.50%, P  = .031 for both conditions). HLA‐B*51:01 was not observed in BD patients with gastrointestinal involvement or arthritis. Furthermore, the AF of HLA‐B*51:01 was significantly higher in HLA‐A*26:01 non‐carrier BD patients without arthritis (17.30% vs 0%, P  = .050). Conclusion: HLA‐B*51:01 was a susceptible allele for Thai BD patients, and associated with posterior uveitis and visual impairment. HLA‐A*26:01 was another susceptible allele in HLA‐B*51X non‐carrier patients. The protective effect of HLA‐B*51:01 on arthritis needs further investigation.